2019
DOI: 10.1016/j.algal.2019.101613
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a spectrophotometric methodology for a rapid iodine analysis in algae and seaweed casts

Abstract: Iodine plays an important role in human metabolism and its deficiency is particularly harmful in pregnancy and childhood. It remains a major public health concern in many countries, especially in Portugal. The main purpose of this work was to develop a validated spectrophotometric analysis for a fast and reliable iodine quantification in algal samples. Absorbance was determined at 410 nm demonstrating a good linearity (R 2 ≈ 1.0) in the range of 0-0.06 mg I/100 g. LOD and LOQ were 1.7 × 10 −3 and 5.0 × 10 −3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A. taxiformis was approximately 3 mg/L, and assuming that a child <3 yr old can drink milk at [36]. Further, [37] reported that approximately 31% of ingested iodine is transferred to milk indicating there is potential that when cows are fed dietary supplements of A. taxiformis, iodine concentrations in milk could be substantially greater than those reported by [14].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A. taxiformis was approximately 3 mg/L, and assuming that a child <3 yr old can drink milk at [36]. Further, [37] reported that approximately 31% of ingested iodine is transferred to milk indicating there is potential that when cows are fed dietary supplements of A. taxiformis, iodine concentrations in milk could be substantially greater than those reported by [14].…”
Section: Resultsmentioning
confidence: 96%
“…In the experiment of [14], the concentration of iodine in milk of cows given 0.5% A. taxiformis was approximately 3 mg/L, and assuming that a child <3 yr old can drink milk at 1 L/d this is approximately 15 times the upper tolerable intake level [35]. Iodine concentrations in A. taxiformis have been reported to range from 8.1 to 11.6 g/kg DM of seaweed [36]. Further, [37] reported that approximately 31% of ingested iodine is transferred to milk indicating there is potential that when cows are fed dietary supplements of A. taxiformis , iodine concentrations in milk could be substantially greater than those reported by [14].…”
Section: Resultsmentioning
confidence: 99%
“…Iodine in algae is volatile and easily reduced or oxidized, so it is challenging to determine the iodine content in seaweed food. The previous study has shown that the spectrophotometric method can quickly and effectively analyze the iodine content in algae samples [ 83 ]. Inductively coupled plasma atomic emission spectrometry (ICP-AES) and inductively coupled plasma mass spectrometry (ICP-MS) have been used to determine iodine concentrations [ 84 , 85 ].…”
Section: Chemical Factors Affecting Food Safety In Algaementioning
confidence: 99%
“…Moreover, phlorotannins are polar metabolites rich in the chemical composition of brown macroalgae, commonly found in Z. tournefortii and species from Dictyopteris genus (Murray et al, 2018;Nunes et al, 2019). According to the mechanism of action, these substances can act at different stages of viral infection and can inhibit adsorption, reverse transcriptase and transcription (Ahn et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…According to Nunes et al (2020), this allows the targeting of bioresources for specific purposes, including functional foods. A viable alternative would be to use this biomass for the extraction of biocompounds for industry intents (Nunes et al, 2019).…”
Section: Centesimal and Chemical Compositionmentioning
confidence: 99%